Evaluation of Perceived Benefits and Risks of Nuclear Technology in Society (Journal of Universal Excellence, 2026)
Research Question (RQ): We would like to know what benefits and risks of the nuclear technology the society is capable of noticing. At the same time, we want to identify the key factors on the basis of which a person builds a perception and opinion about nuclear technology.Purpose: The purpose of the research is evaluated known benefits and risks of nuclear technology society, based on the review of relevant professional and scientific literature.Method: By means of interactive literature review, we wish to make a qualitative content analysis, collect data, study them, evaluate them and create a general trust model.Results: We have found out a key factor for the perception of risks and benefits in nuclear technology. We roughly divided these factors into environmental and social. Environmental factors predominated in the perception of risks, while both were perceived in the benefits.Organization: Understanding public perception is crucial for the development of nuclear energy in the future. The potential benefit of nuclear energy is in the way of clean electricity generation recognized as an approach towards a carbon-free society.Society: The research highlights the link between nuclear technology, society and the environment. It is difficult for people today to live without electricity, so it is interesting to research the fact whether we are willing to live in an environment with a nuclear power plant and accept all its risks.Originality: Based on a review of the literature, we will gain insight into the mindset of society about nuclear technology.Limitations/Future Research: Further research could focus on measures to improve the public mindset for the benefit and support of nuclear development.
Keywords: benefits; risks; trust; nuclear energy; nuclear technology; evaluation; environment